Patients With Alcoholism Functional Changes in the Liver After Covid-19 Disease - Turaev Bobir Temirpulatovich (Peerian Journals Publishing, 2023)
Patients with alcoholism were examined for a state of functional changes in the liver after covid-19. For this, 80 patients who experienced COVID-19, aged 30-45, who stood on the list with a diagnosis of alcoholism, were selected as the main group. They were infected with COVID-19 before the period from 20 to 90 days after their medical history. The control group stood on the list with a diagnosis of 60 alcoholics but was not infected with COVID-19. In the main group of patients included in the study, the activity of blood enzymes increased significantly compared with the control group: it was found that the ALT content increased almost 10 times in the main group, The AST content almost 3 times, LDG 3 times, and Alpine - almost one and a half times. In patients of the main group, the concentration of albumin in peripheral blood decreased. In the ultra-sound examination of the liver, it was found that there are significant changes in the patients of the main group. Patients with alcoholism after covid-19 disease, cytolytic, cholestatic syndrome in the functional hepatobiliary system in the liver, a decrease in the protein synthesis function of the liver was noted. In addition, an increase in the size of the liver, an increase in the diameter of the gate veins, spleen veins and the stiffness of the hepatic parenchyma were found
Keywords: alcoholism; COVID-19; liver; enzyme